Step
*
1
2
2
1
of Lemma
minus-poly-equiv
.....assertion..... 
1. u : iMonomial()
2. v : iMonomial() List
3. (∀i:ℕ||v||. ∀j:ℕi.  imonomial-less(v[j];v[i])) 
⇒ ipolynomial-term(minus-poly(v)) ≡ "-"ipolynomial-term(v)
4. ∀i:ℕ||[u / v]||. ∀j:ℕi.  imonomial-less([u / v][j];[u / v][i])
⊢ ∀i:ℕ||v||. ∀j:ℕi.  imonomial-less(v[j];v[i])
BY
{ (Auto THEN InstHyp [⌜i + 1⌝;⌜j + 1⌝] (-3)⋅ THEN Auto) }
1
1. u : iMonomial()
2. v : iMonomial() List
3. (∀i:ℕ||v||. ∀j:ℕi.  imonomial-less(v[j];v[i])) 
⇒ ipolynomial-term(minus-poly(v)) ≡ "-"ipolynomial-term(v)
4. ∀i:ℕ||[u / v]||. ∀j:ℕi.  imonomial-less([u / v][j];[u / v][i])
5. i : ℕ||v||
6. j : ℕi
7. imonomial-less([u / v][j + 1];[u / v][i + 1])
⊢ imonomial-less(v[j];v[i])
Latex:
Latex:
.....assertion..... 
1.  u  :  iMonomial()
2.  v  :  iMonomial()  List
3.  (\mforall{}i:\mBbbN{}||v||.  \mforall{}j:\mBbbN{}i.    imonomial-less(v[j];v[i]))
{}\mRightarrow{}  ipolynomial-term(minus-poly(v))  \mequiv{}  "-"ipolynomial-term(v)
4.  \mforall{}i:\mBbbN{}||[u  /  v]||.  \mforall{}j:\mBbbN{}i.    imonomial-less([u  /  v][j];[u  /  v][i])
\mvdash{}  \mforall{}i:\mBbbN{}||v||.  \mforall{}j:\mBbbN{}i.    imonomial-less(v[j];v[i])
By
Latex:
(Auto  THEN  InstHyp  [\mkleeneopen{}i  +  1\mkleeneclose{};\mkleeneopen{}j  +  1\mkleeneclose{}]  (-3)\mcdot{}  THEN  Auto)
Home
Index